(untitled) (University Heart Journal, 2009)
Coronary artery disease is the major cause of mortality world wide. The potentially modifiable risk factors for coronary artery disease were increased concentrations of low density lipoprotein cholesterol, decreased concentrations of high density lipoprotein cholesterol, hypertension, hyperglycemia, and smoking. This cross sectional study which included all UGC employees was conducted in the department of cardiology of BSMMU between January 2007 and December 2007. Detailed clinical history, family history, lifestyle, smoking habit, diabetes mellitus, and hypertension, regular use of any medication or any previous cardiac intervention was taken. Physical examination, Blood pressure measurement, ECG, Echocardiography, fasting blood sugar and fasting lipid profile was done to all subjects.163 subjects (all UGC employees), mean age 44.8±8.3 years were included in this study. (20.9%) presented with angina pectoris, 3.7% were having palpitation, and 8.6% were having shortness of breath and 5.5% with nonspecific chest pain. 16.6% subjects presented with hypertension, 12.3% with diabetes mellitus, and 20.9% with dyslipidemia. 3.1% subjects had previous myocardial infarction. ECG shows 8.0% subjects had inferior ischemia, 6.1% had anterior ischemia and 2.5% had bundle branch block. Echocardiography shows 4.9% subjects were having regional wall motion abnormalities Prevalence of risk factors for CAD is increasing, and with the clinical and cost burdens mounting, identifying and treating those at risk remains a national priority. Abbreviations UGC, University Grants Commission, BSMMU, Bangabandhu Sheikh Mujib Medical University doi: 10.3329/uhj.v5i1.3436 University Heart Journal Vol. 5, No. 1, January 2009 20-23